Integrating HIV prevention with family planning services for adolescent girls and young women in Uganda: perspectives of adolescent girls and young women, health care providers, and policymakers - Justine K. Tumusiime; Davina Canagasabey; Peter Mudiope; Sabrina Kitaka; Allen Namagembe; Fiona Walugembe; Bridget Nakankaka; Josephine Nabuuma; Jesca Nasunku; Jane Cover; Betty Mirembe; Ashley Jackson; et al. (Frontiers in Reproductive Health)
IntroductionPersistently high HIV incidence among women, especially adolescent girls and young women (AGYW), have drawn the attention of national policymakers, donors, and implementers in Sub-Saharan Africa to the integration of HIV and family planning (FP) programs. According to several research studies, FP services could offer a holistic strategy to address the HIV and FP needs of this demographic by including HIV prevention approaches, particularly HIV pre-exposure prophylaxis. Our study set out to explore the obstacles and opportunities that AGYW faced in accessing, using, and continuing HIV prevention and contraceptive services; to develop ideas for novel service models that would allow AGYW to receive integrated, HIV prevention and contraception services; and to evaluate the viability, scalability, and acceptability of these models through dialogues with stakeholders using a human-centered design approach.MethodsWe conducted 128 in-depth interviews with 60 AGYW, 24 public and private health care providers, 10 community leaders, and 10 policymakers). We also conducted two co-creation workshops with 50 AGYW and 10 health care providers in Masaka and Nakasongola districts to generate service delivery models.ResultsOur findings reveal various enablers and barriers to the successful integration of HIV prevention into FP services in the areas of policy, human resources and infrastructure, resource management, service delivery, community involvement, supply chain management, and monitoring and reporting.DiscussionSuccessful integration will require addressing key concerns raised by participants in human resource and infrastructure, resource management, service delivery, demand creation, male involvement, supply chain management and monitoring and reporting.